Nada the Lily - Haggard, H. Rider (Henry Rider), 1856-1925 (Salt Lake City, UT : Project Gutenberg, 1998)
"Nada the Lily" by H. Rider Haggard is a historical novel published in 1892. Set during the reign of the legendary Zulu king Chaka, it follows Umslopogaas, the king's unacknowledged son, and his forbidden love for Nada, called the most beautiful of Zulu women. Unusual for its era, the novel features an entirely black South African cast. The tale weaves together history, magic, and tragedy as Umslopogaas joins forces with Galazi the Wolf to command a spectral wolf pack in a story of loyalty, revenge, and doomed romance. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Nada_the_Lily
Release date is 1998-02-01
John Bickers and David Widger
Keywords: Zululand (South Africa) -- Fiction